HISTORISITAS DAN SUMBER TAFSIR KEBAHASAAN DALAM MEMAHAMI BAHASA AL-QURAN - Abd Aziz; Made Saihu (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2022)
This paper aims to describe linguistic interpretation (tafsir lughawi) as a tool in understanding the language of the Koran and sources that can be used as references in the interpretation of the Koran. The types of linguistic interpretations obtained are interpretations with the i'rab Al-Quran approach, nahwu, morphology, sharaf, allegory (amtsal), munasabah, qira'ah. Linguistic interpretation can affect the theological, Sufistic, philosophical, and scientific sides. Linguistic interpretation is also not just understanding the verses of the Koran literally, and of course it can touch social and other aspects, so that the meaning of the verses of the Koran can be fully understood. The interpreter's linguistic ability has an important role in interpreting the Qur'an. The consequence of the inclusion of Arabic as the language of the Koran causes variations in understanding in linguistic interpretation. Methods and linguistic analysis cannot be separated from the tendency of the interpreter, and this is a separate place for the reader